2013
DOI: 10.1155/2013/835610
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Glycols as Efficient Catalysts for the Oxidation of Xanthine Alkaloids by Ceric Ammonium Nitrate in Acetonitrile: A Kinetic and Mechanistic Approach

Abstract: Kinetics of oxidation of xanthine alkaloids, such as Xanthine (XAN), hypoxanthine (HXAN), caffeine (CAF), theophylline (TPL), and theobromine (TBR), have been studied with ceric ammonium nitrate (CAN) using poly ethylene glycols (PEG) as catalysts. Reaction obeyed first order kinetics in both [CAN] and [Xanthine alkaloid]. Highly sluggish CAN-xanthine alkaloid reactions (in acetonitrile media even at elevated temperatures) are enhanced in presence PEGs (PEG-200, -300, -400, -600). An increase in [PEG] increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…However, the PEG chains in aqueous media are analogous to the structure of nonionic micelles of Triton-X and Tween 20. Consequently, the catalytic impact of PEGs on the kinetics of reactions could be explicated via the cooperative Piszkiewicz model [11,[19][20][21]. In this work, the model has been employed to investigate the effect of the presence of the very low concentrations of the polymers and surfactants in the reaction media through the interactions of the maltose molecules with the polymer or surfactant micelles to increase the concentration of maltose molecules inside the micelles, which behave as nanoreactors in the aqueous medium.…”
Section: Effect Of Saltsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the PEG chains in aqueous media are analogous to the structure of nonionic micelles of Triton-X and Tween 20. Consequently, the catalytic impact of PEGs on the kinetics of reactions could be explicated via the cooperative Piszkiewicz model [11,[19][20][21]. In this work, the model has been employed to investigate the effect of the presence of the very low concentrations of the polymers and surfactants in the reaction media through the interactions of the maltose molecules with the polymer or surfactant micelles to increase the concentration of maltose molecules inside the micelles, which behave as nanoreactors in the aqueous medium.…”
Section: Effect Of Saltsmentioning
confidence: 99%
“…Shylaja et al used PEGs to catalyze the reactions of some xanthine alkaloids with ceric ammonium nitrate to give uric acid derivatives. ey found that the rate of reaction increased linearly in the presence of a set of PEGs, and their catalytic activities depended on the nature as well as the molecular weight of the PEGs [11]. Likewise, PEGs catalyzed the reaction of borneol, isoborneol, and camphor with ceric ammonium nitrate acid-free conditions.…”
Section: Introductionmentioning
confidence: 96%
“…While PEO use is almost relegated to biomedical and healthcare applications [ 43 , 44 , 45 , 46 , 47 , 48 , 49 ], its usage in other fields is uncommon, such as in composite laminates for hindering delamination [ 36 ] and as phase change materials (PCMs) [ 50 ]. Even PEO application in catalysis is limited to a few reported cases [ 51 , 52 , 53 ]; however, it has never been shaped into nanofibers for catalytic purposes.…”
Section: Introductionmentioning
confidence: 99%
“…One of these polymeric materials is polyethylene glycol (PEG), which has attracted the attention of several researchers studying catalytic behaviour. 13,14 In this study, we investigated the kinetics of the permanganate ion oxidation of L-lysine in a perchloric acid medium. The reaction was already studied in an alkaline medium, where the product was reported to contain decarboxylated residue.…”
Section: Introductionmentioning
confidence: 99%